Personality-Oriented Focus English Lesson Activities of The Teacher and Students - Ismoilova Zarifa (European Science Publishing, 2023)
The article reveals the features of the teacher's activity and students in an English lesson with a personality-orientation, as well as the main aspects of their own research on improving the educational process and the effectiveness of training
Keywords: approach, effect, effectiveness of learning, individual and group, new forms of education